1991
DOI: 10.3171/jns.1991.74.2.0258
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow patterns at major vessel bifurcations and aneurysms in rats

Abstract: Cerebral arterial bifurcations in rats were treated to induce cerebral aneurysms experimentally, and flow patterns of latex particles introduced under a constant flow rate were analyzed with a 16-mm cine-camera and videocassette recorder. Cerebral aneurysms were produced by ligating one common carotid artery, inducing experimental hypertension, and feeding the animals beta-aminopropionitrile. After perfusion and fixation, samples of cerebral arterial bifurcations with shallow invaginations and with small aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 17 publications
4
69
0
Order By: Relevance
“…5). Most high WSS concentrates near the distal neck region of the aneurysm, which is consistent with previous reports (23), (28), (29) . So the aneurysm first develops toward the distal neck region, and as the aneurysm enlarges, the previous distal neck region becomes part of the aneurysm sac.…”
Section: Discussionsupporting
confidence: 82%
“…5). Most high WSS concentrates near the distal neck region of the aneurysm, which is consistent with previous reports (23), (28), (29) . So the aneurysm first develops toward the distal neck region, and as the aneurysm enlarges, the previous distal neck region becomes part of the aneurysm sac.…”
Section: Discussionsupporting
confidence: 82%
“…One likely explanation is that iNOS is induced in response to an excessive increase in wall shear stress. We have shown that the wall shear stress at the distal end of the JAG is highest during the early development of aneurysms 10,11 and that the initial dilatation of the arterial wall develops at this area. 3 BX had a significant amelioration of EC and SMC damage (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Our hemorheological studies in rat aneurysms showed that in early aneurysm development, the wall shear stress was increased and highest at the distal end of the JAG, the distal end of the aneurysmal orifice. 10,11 Moreover, the initial dilatation and degeneration of the arterial wall invariably developed in the same area. 3 Other investigators have also indicated that the wall shear stress is the highest at the aneurysmal end.…”
mentioning
confidence: 99%
“…29,32,35,36 By contrast, high WSS, which is associated with high blood flow, can lead to dysfunction of the endothelium, with progressive deformation of the wall until rupture occurs. 31,37 Meng et al 38 recently demonstrated in an animal model that high WSS contributes to aneurysmal initiation and development. They found that areas with high WSS and high WSS spatial gradients were associated with remodeling of the wall of an aneurysm, such as disrupted internal elastic lamina and endothelium, thinned media, and smooth muscle cell loss.…”
Section: Discussionmentioning
confidence: 99%
“…The role of WSS in cytologic changes of the arterial walls and the variable geometry of the arterial system have been found to be critical in the onset of vascular diseases, such as aneurysmal lesions or atherosclerotic phenomena. 16,20,21,[28][29][30][31][32][33][34] The role of WSS is still controversial in the development and growth of cerebral aneurysms [16][17][18] ; in fact, both excess and lack of WSS can lead to pathologic phenomena that cause changes in the biomechanical properties of the arterial wall. 29 The presence of a low-flow environment leads to regions of low WSS (Ͻ0.4 Pa), which can be detrimental to the vessel endothelium.…”
Section: Discussionmentioning
confidence: 99%